The Crime Of Counterfeiting Commercial Brands From The Perspective Of Islamic Jurisprudence And Its Impact On Sustainable Development And Health - Salem Farhat, Ali Ahmed; Hammoud Azzoun, Jamal Lakhdar; Youssef Saadiya, Ahmed (Journal of neonatal surgery, 2025)
The research aims to define commercial brands, examine the ruling on counterfeiting them from the perspective of Islamic jurisprudence, analyse the consequences of brand counterfeiting, determine the penalty for counterfeiting well-known trademarks and selling them as originals, and evaluate the legal and religious implications of such practices. The study adopts a descriptive methodology, relying on an analytical approach, and has led to several significant findings, the most notable of which are as follows: A commercial brand refers to the identity of a company or product that distinguishes it from competitors. It represents the reputation and image of the company in the minds of customers and the public. A trade name refers to the designation used by a merchant as a distinctive mark for their business, allowing consumers to identify a particular type of goods, service, or quality. A brand is broader and more comprehensive than a trade name, as it encompasses reputation, marketing, corporate image, and influence, rather than just the name itself. The concept of the crime of counterfeiting commercial brands from the perspective of Islamic jurisprudence refers to the act of producing an imitation of an original product with lower quality, with the intention of deceiving, defrauding, falsifying, and exploiting consumers for quick financial gain. Its punishment falls under commercial fraud under Saudi law. Among the means of proving this crime is reporting the counterfeit product to the Ministry with all relevant details. The penalty for counterfeiting commercial brands is classified under fraud, trademark infringement, and brand counterfeiting, which are considered financial offences. Any individual who commits such an offence is subject to a fine not exceeding five hundred thousand (500,000) Saudi Riyals, imprisonment for a period not exceeding two years, or both penalties combined. Counterfeiting and fraudulent use of commercial brands have a negative impact on sustainable development and economic growth.